Development of an innovative educational escape game to promote teamwork in dentistry. (18th February 2021) - Zaug, Pernilla; Gros, Catherine‐Isabelle; Wagner, Delphine; Pilavyan, Elise; Meyer, Florent; Offner, Damien; Strub, Marion
Abstract: Background: Escape games have proven to be an innovative pedagogical tool that allows students to use the professional skills they acquired. The appeal of the game lies in the stimulation of the players' minds and in the diversity of the puzzles. Purpose/objectives: To evaluate the effectiveness of an educational tool aimed at cultivating team spirit and group cohesion in dentistry students through a fun collaborative activity that mobilises their knowledge and skills. Materials and method: Twenty‐four students participated to the escape game over a one‐day period. In order to win, they had to solve dentistry‐related puzzles. Results: Feedback was strongly positive. The balance between manipulations and theoretical questions stimulated them. Students did favour this type of activity which allows to increase interactions between students as well as with the teaching team. Conclusion: Escape games in dental schools foster a supportive learning environment and stimulated students' motivation and group cohesion.